Analisis pengaruh media sosial terhadap kesejahteraan mental dengan menggunakan regresi dan korelasi - Putri Adi Permana, Belinda; Halim Limantoro, Alberto (Fakultas Teknologi Informasi, Universitas Kristen Satya Wacana, 2025)
This study aims to explore the influence of social media on mental well-being, focusing on a quantitative analysis using simple linear regression. Social media has become an integral part of daily life, affecting various aspects of individual life, including mental well-being. This study collected data from an online survey participated by respondents from diverse demographics, measuring social media usage and mental well-being indicators such as stress levels, anxiety, and life satisfaction. Through simple linear regression analysis, this study examined the relationship between social media usage duration and changes in mental well-being. Preliminary findings indicate a significant correlation between social media usage intensity and increased stress and anxiety levels, as well as decreased life satisfaction. These findings are expected to provide insights for policymakers and mental health practitioners to develop more effective strategies in managing the negative impacts of social media and enhancing mental well-being in society.